I sistemi locali turistici in Italia - Francesco, Capone (Scuole di dottorato, 2005)
In recent decades tourism has become one of the most important industries in the global economy. Consequently, the study of tourist destinations is increasingly seen as a critical element in the competitiveness of countries with a tourist vocation. The goal of this study was primarily to identify what the local tourist systems in Italy are, and how they compete among themselves. Through the application of the Istat-Sforzi method and the techniques of spatial econometrics, the book offers a broad panorama of cartographic illustrations of the Italian destinations, elaborating an analysis proxy to empirically measure the sources of competitiveness of these systems of enterprise, concentrating in particular on the extended tourist chain and on the destination networks.